Bioengineering an electro-mechanically functional miniature ventricular heart chamber from human pluripotent stem cells. (May 2018) - Li, Ronald A.; Keung, Wendy; Cashman, Timothy J.; Backeris, Peter C.; Johnson, Bryce V.; Bardot, Evan S.; Wong, Andy O.T.; Chan, Patrick K.W.; Chan, Camie W.Y.; Costa, Kevin D.
Abstract: Tissue engineers and stem cell biologists have made exciting progress toward creating simplified models of human heart muscles or aligned monolayers to help bridge a longstanding gap between experimental animals and clinical trials. However, no existing human in vitro systems provide the direct measures of cardiac performance as a pump. Here, we developed a next-generation in vitro biomimetic model of pumping human heart chamber, and demonstrated its capability for pharmaceutical testing. From human pluripotent stem cell (hPSC)-derived ventricular cardiomyocytes (hvCM) embedded in collagen-based extracellular matrix hydrogel, we engineered a three-dimensional (3D) electro-mechanically coupled, fluid-ejecting miniature human ventricle-like cardiac organoid chamber (hvCOC). Structural characterization showed organized sarcomeres with myofibrillar microstructures. Transcript and RNA-seq analyses revealed upregulation of key Ca 2+ -handling, ion channel, and cardiac-specific proteins in hvCOC compared to lower-order 2D and 3D cultures of the same constituent cells. Clinically-important, physiologically complex contractile parameters such as ejection fraction, developed pressure, and stroke work, as well as electrophysiological properties including action potential and conduction velocity were measured: hvCOC displayed key molecular and physiological characteristics of the native ventricle, and showed expected mechanical and electrophysiological responses to a range of pharmacological interventions (including positive and negative inotropes). We conclude that such "human-heart-in-a-jar" technology could facilitate the drug discovery process by providing human-specific preclinical data during early stage drug development.